2016
DOI: 10.5937/str1601018f
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chemical stability of propellants using the vacuum stability test method

Abstract: This paper includes the results of the examination of the single base propellants, double base propellants and double base rocket propellants with the Czech Vacuum Stability Test STABIL. For this method the main term was to analyze and define the best options for preparation of the samples, selection of the optimal mass of the samples and conditions of examination. Chemical stability of these samples was determined according to the STANAG 4556 standard method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The volume of gas liberated upon heating was greater than the stability limit of commercial nitrocellulose≤2 cm 3 g −1 (Fidanovski et al 2016) confirming that the improvised nitrocellulose is less stable than commercial nitrocellulose manufactured using common nitrating agents. The Vacuum Stability results from a commercial nitrocellulose containing 12.6% N showed a gas evolution of 1.7 cm 3 g −1 suggesting that the stability of improvised NC is slightly poorer than the commercial grade nitrocellulose (Table 3).…”
Section: Vacuum Stability Testmentioning
confidence: 87%
“…The volume of gas liberated upon heating was greater than the stability limit of commercial nitrocellulose≤2 cm 3 g −1 (Fidanovski et al 2016) confirming that the improvised nitrocellulose is less stable than commercial nitrocellulose manufactured using common nitrating agents. The Vacuum Stability results from a commercial nitrocellulose containing 12.6% N showed a gas evolution of 1.7 cm 3 g −1 suggesting that the stability of improvised NC is slightly poorer than the commercial grade nitrocellulose (Table 3).…”
Section: Vacuum Stability Testmentioning
confidence: 87%
“…A Shimadzu spectrometer 8400S was used to analyze the propellant samples embedded in KBr pellets. All the sam-ples have been dried in advance for 4 h in an oven at 333.15 � 0.1 K. These conditions (drying time and temperature) were found optimal to remove moisture before the investigation of different types of propellants including double-base rocket propellants [23]. All the measurements have been carried out at room temperature.…”
Section: Ftir Measurementmentioning
confidence: 99%
“…The mean particle size of about 300 μm was determined, and it was also found that two main sizes dominate (75 and 700 μm). In general, the method of determining the mean particle size of the mixture is complex and not reliable, and it is actual wherever the problem of small particles is present [10,11].…”
Section: Separation Of Different Mixture Granulationsmentioning
confidence: 99%